Six Sigma Improvement Project for Automotive Speakers in an Assembly Process - Valles, Adan; Noriega, Salvador; Sanchez, Jaime; Martinez, Erwin; Salinas, Jesús (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Optima; panose-1:2 0 5 3 6 0 0 2 0 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> This Six Sigma application examined an automotive speaker production process in a multinational corporation twin plant. The process was a semiautomatic assembly operation. A six index assembler chemically bonded a coil to a diaphragm. The problem is described in the first part of the paper, which pinpoints the separation between those two parts. This is a critical process characteristic that was not properly controlled. Operations were malfunctioning. High scrap and rework rates, and high levels of in process inventory as well as inspection stations all contributed to the problem. Variables were measured to determine the problem with accuracy. The fixture and tool capabilities were estimated in the analysis as well. The authors found that the large variation could be attributed to the product and operator procedure. Variation in the product was determined to be explained by unsuitable fixtures and tools. This resulted in having the fixtures and tools re-dimensioned and re-designed. Measurements were then taken to determine whether the improved process design would make significant contributions. A control process and operating procedures were established to insure that the initial process conditions would not be repeated. <!--EndFragment-->